1989
DOI: 10.1148/radiology.173.1.2528782
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte retrieval in an in vitro fertilization-embryo transfer program: comparison of four methods.

Abstract: The records of 191 patients involved in 316 treatment cycles over 3 years in an in vitro fertilization-embryo transfer program were reviewed. Follicular aspiration, oocyte retrieval, pregnancy rates, technical difficulty, and complications were compared in four oocyte retrieval methods: 117 laparoscopic retrievals, 116 ultrasound (US)-guided percutaneous transvesical retrievals, 43 US-guided transvaginal retrievals, and 40 combined US and laparoscopic retrievals. The mean number of aspirated follicles (9.14) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Her uterus showed bicornuate uterus and her fallopian tube was elongated Fig. 2 Results of the patient's pelvic MRI, which confirms the position and location, in the upper pelvic cavity, of the bilateral ovaries which were attached to the area above the common iliac vessels ultrasound-guided technique with that using the laparoscopic technique, and reported that the former outperformed the latter [2]. Recently, however, some cases of patients with ovarian malposition who underwent ultrasound-guided transabdominal oocyte retrieval have been reported [3,4].…”
Section: Commentsmentioning
confidence: 54%
“…Her uterus showed bicornuate uterus and her fallopian tube was elongated Fig. 2 Results of the patient's pelvic MRI, which confirms the position and location, in the upper pelvic cavity, of the bilateral ovaries which were attached to the area above the common iliac vessels ultrasound-guided technique with that using the laparoscopic technique, and reported that the former outperformed the latter [2]. Recently, however, some cases of patients with ovarian malposition who underwent ultrasound-guided transabdominal oocyte retrieval have been reported [3,4].…”
Section: Commentsmentioning
confidence: 54%
“…Laparoscopy was soon replaced by transvaginal retrieval under ultrasound guidance as the primary route to obtain oocytes for assisted reproductive technologies (ART) due to its safety, effectiveness, and the avoidance of general anesthesia [3][4][5][6]. The conversion to a transvaginal retrieval approach was followed by refinements in the oocyte retrieval needle design in an effort to maximize recovery and minimize patient discomfort [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the laparoscopic method is a tedious and time-consuming procedure due to the complicated experimental setup (Flood et al, 1989;Bavister, 2004). Furthermore, laparoscopic oocyte retrieval is only possible when the ovarian cortex is partly exposed and follicles are visible under the surface (Wiseman et al, 1989). The ultrasound-guided follicle aspiration procedure represents a better alternative to the other two methods in terms of reduced invasiveness, infection risk and other potential detrimental effects, work involved, and post-operative recovery (Seifer et al, 1988;Flood et al, 1989;Wiseman et al, 1989).…”
Section: Introductionmentioning
confidence: 99%